2017
DOI: 10.1055/s-0043-120672
|View full text |Cite
|
Sign up to set email alerts
|

The Latest Developments of Functional Molecular Imaging in the Diagnosis of Primary Aldosteronism

Abstract: Differentiation of unilateral from bilateral aldosterone hypersecretion is the essential step in the clinical practice of primary aldosteronism (PA). Although adrenal venous sampling (AVS) has been established as the most standard test recommended by the guideline, its invasive and technically difficult nature has facilitated the approach to develop non-invasive functioning imaging as an alternative test. Compared to the conventional adrenocortical scintigraphy with cholesterol derivatives as tracer, the first… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…Positron emission tomography (PET)-CT using radiotracer 11 Cmetomidate, an inhibitor of 11β-hydroxylase and aldosterone synthase, was demonstrated as a potential non-invasive alternative to AVS [103]. The high specificity and affinity of 11 C-metomidate to CYP11B enzymes permit distinguishing cortical masses from medullary masses, and dexamethasone prior to imaging increased the difference of maximum standardised uptake values between tumour and normal adrenal by 25.6% (P < 0.01) which was absent in BAH, thereby differentiating unilateral from bilateral PA [104,105]. A recent study reported that a treatment decision based on 11 C-metomidate PET-CT achieved biochemical cure in of 4 patients with PA [106].…”
Section: D) Future Approaches For Subtype Differentiationmentioning
confidence: 99%
“…Positron emission tomography (PET)-CT using radiotracer 11 Cmetomidate, an inhibitor of 11β-hydroxylase and aldosterone synthase, was demonstrated as a potential non-invasive alternative to AVS [103]. The high specificity and affinity of 11 C-metomidate to CYP11B enzymes permit distinguishing cortical masses from medullary masses, and dexamethasone prior to imaging increased the difference of maximum standardised uptake values between tumour and normal adrenal by 25.6% (P < 0.01) which was absent in BAH, thereby differentiating unilateral from bilateral PA [104,105]. A recent study reported that a treatment decision based on 11 C-metomidate PET-CT achieved biochemical cure in of 4 patients with PA [106].…”
Section: D) Future Approaches For Subtype Differentiationmentioning
confidence: 99%
“…In another study on patients with unilateral APA (diagnosed by AVS) with follow-up data, 36% of patients who were biochemically cured after adrenalectomy would have been misdiagnosed on the basis of CT results [40]. Thus, neither CT nor AVS are completely reliable and strong interest focusses on approaches to improve the performance and accessibility of subtype differentiation in PA [[12], [13], [14], [15], [16], [17]]. The potential utility of adrenal steroids in discriminating different subtypes of PA has been investigated in numerous studies with attention centering on the hybrid steroids 18-oxocortisol and 18-hydroxycortisol in urine or plasma [42].…”
Section: Discussionmentioning
confidence: 99%
“…The sensitivity of CT imaging is often insufficient for the identification of APAs less than 10 mm in diameter, while AVS displays high sensitivity and specificity (95% and 100%, respectively) to distinguish unilateral from bilateral PA [9,10]. AVS is a technically-demanding and invasive procedure with non-standardized protocols and variable interpretation of results, and alternative approaches to reduce or even replace AVS for subtype differentiation in PA are currently sought [[11], [12], [13], [14], [15], [16]].…”
Section: Introductionmentioning
confidence: 99%
“…Within the last couple of years, a special focus was given to endocrine tumors, e. g. of the neuroendocrine system including pituitary tumors and pheochromocytoma / paraganglioma. In addition, three issues were published on primary hyperaldosteronism focusing on the genetic cause of the disease as well as diagnostic and therapeutic options [2][3][4][5][6][7][8][9][10][11][12][13][14][15].…”
Section: Dear Readersmentioning
confidence: 99%